2020
DOI: 10.1007/s42773-020-00054-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrochar from biogas digestate on soil improvement and plant growth aspects

Abstract: Hydrochar (HC), produced by hydrothermal carbonization, offers technical advantages over biochar (BC) produced by pyrolysis, and is suitable for soil amelioration, carbon sequestration, and enhanced plant growth. BC grain size has been shown to influence nutrient retention, microbial colonization and aggregate formation; however, similar research for HC is lacking. Pot trials were conducted to investigate the influence of HC grain size [coarse (6.3-2 mm), medium (2-0.63 mm) and fine (< 0.63 mm)], produced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 69 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Moreover, different studies demonstrated also the positive effect of hydrochar on the retention of pesticides, allowing an optimized utilization and reducing the possible risk of leakage and contamination of ground waters [156][157][158]. The fast mineralization of the carbon contained in the char leads to a short-term release of nutrients in the soil, reducing the carbon content by 30-40% within the first 12-19 months [159][160][161].…”
Section: Soil Conditioningmentioning
confidence: 99%
“…Moreover, different studies demonstrated also the positive effect of hydrochar on the retention of pesticides, allowing an optimized utilization and reducing the possible risk of leakage and contamination of ground waters [156][157][158]. The fast mineralization of the carbon contained in the char leads to a short-term release of nutrients in the soil, reducing the carbon content by 30-40% within the first 12-19 months [159][160][161].…”
Section: Soil Conditioningmentioning
confidence: 99%
“…[322][323] Moreover, HTC carbon materials are suitable for soils with different textures, such as clay, sandy soils, and loamy soils. [322,[324][325] They also prove beneficial for highly weathered soils with unfavorable chemical properties, such as high pH levels and low cation exchange capacity (CEC). [326][327] The presence of acidic functional groups in HTC carbon materials allows them to effectively lower soil pH levels, particularly in alkaline and calcareous soils.…”
Section: Soil Amendmentmentioning
confidence: 99%
“…In addition, the application of hydrochar from urban biowaste on soil may raise crop productivity and nutrient availability [21]. These benefits have been described in soils with a wide range of textures, such as clay, loamy, and sandy soils [17,19,22]. However, direct application of biochar and hydrochar can also have an adverse impact on seed germination and plant growth since, depending on the source and operating conditions, hazardous chemicals may be present on their surfaces.…”
Section: Introductionmentioning
confidence: 99%